Fundamentals of semiconductor fabrication - May, Gary S. (Wiley, 2004)
This concise introduction to semiconductor fabrication technology covers everything professionals need to know, from crystal growth to integrated devices and circuits. Throughout, the authors address both theory and the practical aspects of each major fabrication step, including crystal growth, silicon oxidation, photolithography, etching, diffusion, ion implantation, and thin film depositio